Management of Subdural Hematohygromas in Abusive Head Trauma. Issue 2 (10th April 2019) - Nguyen, Vincent N; Wallace, David; Ajmera, Sonia; Akinduro, Oluwatomi; Smith, Lydia J; Giles, Kim; Vaughn, Brandy; Klimo, Paul
Abstract: BACKGROUND: The optimal management of nonacute subdural fluid collections in infantile abusive head trauma (AHT) remains controversial. OBJECTIVE: To review the outcomes and costs of the various treatments for symptomatic subdural fluid collections in children with AHT at a single center. METHODS: Our AHT database was queried to identify children requiring any intervention for hematohygromas. Demographic, hospital course, radiologic, cost, readmission, and follow-up information were collected. RESULTS: From January 2009 to March 2018, the authors identified 318 children with AHT, of whom 210 (66%) had a subdural collection of any type (blood or cerebrospinal fluid). A total of 50 required some form of intervention specifically for chronic hematohygromas. The initial management consisted of transfontanelle percutaneous aspiration ( n  = 31), burr holes with ( n  = 12) or without ( n  = 3) external subdural drainage, and mini-craniotomy ( n  = 4). Of those who were initially managed with 1 or more needle aspiration, 23 (74%) required further intervention—12 subduroperitoneal shunts and 11 nonshunt procedures. No patient who underwent burr holes/external drainage required further intervention ( n  = 16). Overall, the average number of interventions needed in these 50 children for definitive treatment was 1.8 (range, 1-4). A total of 15 children ultimately required a subduroperitoneal shunt. Complications (infectious, hemorrhagic, and thrombotic) were significant and occurred in all treatment groups except burr holes without drainage ( n  = 3). The average hospital charge for the entire cohort was $166 300.25 (range, $19 126-$739 248). CONCLUSION: Based on our experience to date, burr hole with controlled external subdural drainage is an effective and preferred treatment for traumatic hematohygromas; complications and need for additional intervention is low.